Design and develop a mechanical keyboard - Koh, Destin Seng Wei (Nanyang Technological University, 2021)
Keyboards are the interface that users use to interact with the digital realm through their personal computers. There have been improvements made to designs of keyboards, such as having integrated wrist rests to improve ergonomics, and even interesting layouts such as split keyboards or Alice layout keyboards that are meant to be more ergonomic for users. However, the design of most mass-produced keyboards has remained relatively unchanged. The aim of this project is to produce a keyboard that remains relatively unchanged in terms of aesthetics and layout but have improved ergonomics for users by providing a softer typing experience. In this project, the keyboard produced utilises a new mounting system for the mounting plate and printed circuit board (PCB). Randomly picked users are asked to test the newly developed keyboard to see if the changes made in the design are apparent during use and whether further improvements can be made. Results show that users are pleased with the developed product as keypresses are not as harsh compared to most mass-produced keyboards, with users declaring that they would prefer using the keyboard developed in this project over ones that they currently possess. Users also note that the sound profile of the keyboard is very pleasing. It is also noted that the price of the keyboard is very important in determining whether users would purchase a keyboard such as the keyboard developed in this project. Future developments of the keyboard would incorporate the feedback received from this project to reach a state that is satisfactory for a larger market.